Radial transport dynamics studies of SMBI with a newly developed TPSMBI code - 王亚辉 郭文峰 王占辉 任启龙 孙爱萍 许敏 王爱科 项农 (Chinese physics B, 2016)
In tokamak plasma fueling, supersonic molecule beam injection(SMBI) with a higher fueling efficiency and a deeper penetration depth than the traditional gas puffing method has been developed and widely applied to many tokamak devices.It is crucial to study the transport dynamics of SMBI to improve its fueling efficiency, especially in the high confinement regime. A new one-dimensional(1D) code of TPSMBI has also been developed recently based on a six-field SMBI model in cylindrical coordinate. It couples plasma density and heat radial transport equations together with neutral density transport equations for both molecules and atoms and momentum radial transport equations for molecules. The dominant particle collisional interactions between plasmas and neutrals, such as molecule dissociation, atom ionization and charge-exchange effects, are included in the model. The code is verified to be correct with analytical solutions and also benchmarked well with the trans-neut module of BOUT++ code. Time-dependent radial transport dynamics and mean profile evolution are studied during SMBI with the TPSMBI code in both slab and cylindrical coordinates. Along the SMBI path, plasma density increases due to particle fuelling, while plasma temperature decreases due to heat cooling. Being different from slab coordinate, the curvature effect leads to larger front densities of molecule and atom during SMBI in cylindrical coordinate simulation.